2010
DOI: 10.4315/0362-028x-73.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Sampling of Carcasses by Excision or Swabbing with Three Types of Sponge or Gauze

Abstract: Fifty-five bovine, 50 equine, 60 ovine, and 50 porcine carcasses were sampled in a slaughterhouse in eastern Spain. Two samples were taken from each carcass, one using the excision method and the other using the swabbing method. Four different materials were used for swabbing: cellulose, polyurethane, or viscose sponges, and medical gauze. Samples were collected at the end of the process by four different people before the carcasses were taken to the cooler. The samples were examined for total viable bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…This is in line with other studies carried out on pig carcases (Ghafir & Daube, 2008;Lindblad, 2007;Martinez, Celda, Anastasio, Garcia, & Lopez-Mendoza, 2010;Pepperell et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with other studies carried out on pig carcases (Ghafir & Daube, 2008;Lindblad, 2007;Martinez, Celda, Anastasio, Garcia, & Lopez-Mendoza, 2010;Pepperell et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Bacterial recovery from carcass surfaces depends on the sampling method used (Dorsa et al, 1996;Fliss et al, 1991;Gill et al, 2001;Martinez et al, 2010). It has also been reported that excision can recover the largest number of bacteria from a given area of carcass surface (Sharpe et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken after rapid cooling of the carcasses. S. aureus is able to bind strongly to corneocytes, which could imply that sponge swabbing might not be sufficient to collect all MRSA present and a more destructive method, such as cutting of slices is needed as was reported for Salmonella or E. coli (Ghafir and Daube, 2008;Martinez et al, 2010). Another possibility could be the reduced viability of MRSA after cooling of the carcasses, even though S. aureus is able to persist colder temperatures (Onyango et al, 2012).…”
Section: Resultsmentioning
confidence: 99%